Pt-w based catalysts, methods of making and using the same, and selective hydrogenolysis reactions

CN122999190APending Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510557530.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]本发明的目的是为了克服现有技术存在的催化剂催化活性和水热稳定性较差,贵金属容易流失导致催化活性快速降低的问题,提供一种Pt-W基催化剂及其制备方法与应用、选择性氢解反应,该催化剂具有高催化活性和高稳定性,能够长周期稳定运行

Benefits of technology

[0027](1)本发明提供的Pt-W基催化剂,具有高催化活性和高稳定性,能够长周期稳定运行;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999190A_ABST
    Figure CN122999190A_ABST
Patent Text Reader

Abstract

The application relates to the field of catalyst material synthesis, and discloses a Pt-W-based catalyst and a preparation method and application thereof, a selective hydrogenolysis reaction, wherein the catalyst comprises Pt nanoparticles, alumina and W oxide; the Pt nanoparticles are confined in the alumina, and the W oxide is loaded on the surface of the alumina. The catalyst has high catalytic activity and high stability, and can be stably operated for a long period.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst material synthesis, specifically to a Pt-W-based catalyst, its preparation method and application, and selective hydrogenolysis reaction. Background Technology

[0002] Renewable energy is one of the most promising new energy sources. Among them, 1,3-propanediol, 1,5-pentanediol, and 1,6-hexanediol are important chemical intermediates and key monomers for the synthesis of high-end polyesters. Currently, the industrial production of 1,3-propanediol, 1,5-pentanediol, and 1,6-hexanediol mainly uses petroleum refining, which has problems such as high energy consumption, non-renewable raw materials, difficulty in separating reaction products, and environmental pollution.

[0003] A method for the catalytic conversion of glycerol to 1,3-propanediol was reported in the literature (Chinese Journal of Catalysis, 2020, 41, 1261-1267), and the stability of the Pt-W-based catalyst was investigated after 700 hours of continuous operation in a fixed-bed reactor. After 700 hours of reaction, the glycerol conversion decreased from the initial 58% to 25%, and the loss of the precious metal Pt content reached 8.7 wt%.

[0004] The literature (ACS Catal. 2018, 8, 1427-1439) reports a method for selective hydrogenolysis of tetrahydrofurandiethanol to 1,6-hexanediol using a Pt-W-based catalyst, with a 1,6-hexanediol yield of up to 70%. However, the Pt content is as high as 10%, and no reports on catalyst stability have been found.

[0005] The literature (Catalysis Today, 2018, 303, 207-212) reports a method for selective hydrogenolysis of tetrahydrofurfural to 1,5-pentanediol using a Pt-W-based catalyst. The maximum yield of 1,5-pentanediol is 43%, with a Pt content of 3%. No reports on catalyst stability have been found.

[0006] The industrial preparation of 1,3-propanediol, 1,5-pentanediol, and 1,6-hexanediol typically utilizes bio-based platform compounds such as glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandimethyl alcohol. Under the catalysis of Pt-W-based catalysts, these compounds can all undergo selective hydrogenolysis of secondary hydroxyl groups. While existing technologies can achieve these catalytic reactions, the reaction conditions are quite demanding, usually requiring high temperatures in an aqueous phase. Furthermore, they place high requirements on catalyst activity and hydrothermal stability, hindering widespread industrial application. Therefore, catalysts that balance catalytic activity and stability are needed. Summary of the Invention

[0007] The purpose of this invention is to overcome the problems of poor catalytic activity and hydrothermal stability of existing catalysts, and the rapid decrease in catalytic activity due to the easy loss of precious metals. This invention provides a Pt-W-based catalyst, its preparation method and application, and selective hydrogenolysis reaction. This catalyst has high catalytic activity and high stability, and can operate stably for a long period of time.

[0008] To achieve the above objectives, the first aspect of the present invention provides a Pt-W-based catalyst, wherein the catalyst comprises Pt nanoparticles, alumina, and W oxide;

[0009] The Pt nanoparticles are confined in alumina, and the W oxide is loaded on the surface of alumina.

[0010] Preferably, the average particle size of the Pt nanoparticles is 0.5-6 nm, and more preferably 2-4 nm.

[0011] Preferably, the Pt nanoparticles comprise 0.3-4% by weight, more preferably 0.5-3% by weight, based on the total weight of the catalyst.

[0012] Preferably, the content of W oxide is 0.3-10% by weight, more preferably 3-8% by weight, based on the total weight of the catalyst.

[0013] A second aspect of the present invention provides a method for preparing a Pt-W-based catalyst, wherein the method comprises:

[0014] (1) Load Pt nanoparticles onto an organic framework to obtain a pre-formed Pt-containing organic framework;

[0015] (2) Grow an organic framework on the surface of the pre-formed Pt-containing organic framework in step (1) to obtain an organic framework for encapsulating Pt particles.

[0016] (3) Fill the organic framework of the encapsulated Pt particles obtained in step (2) with alumina to obtain Pt@Al2O3 material;

[0017] (4) Load W oxide onto the surface of Pt@Al2O3 material and perform heat treatment to obtain Pt-W-based catalyst.

[0018] Preferably, in step (1), the method for preparing the Pt nanoparticles includes:

[0019] After a first heating of a mixture containing a platinum source and an organic solvent, it is mixed with a reducing agent and then heated a second time to obtain Pt nanoparticles.

[0020] Preferably, in step (1), the loading method includes: mixing Pt nanoparticles with an organic framework, separating the solid and liquid phases, and then subjecting the obtained solid product to a first calcination to obtain a pre-formed Pt-containing organic framework.

[0021] Preferably, step (4) includes: mixing the Pt@Al2O3 material with a solution containing a tungsten source and performing heat treatment.

[0022] Preferably, the tungsten source, calculated as W oxide, has a mass ratio of 0.003-0.1:1 to Pt@Al2O3 material, more preferably 0.03-0.08:1.

[0023] The third aspect of this invention provides a Pt-W-based catalyst prepared by the preparation method described in the second aspect.

[0024] The fourth aspect of this invention provides the application of the Pt-W-based catalyst described in the first or third aspect in a hydrogenolysis reaction.

[0025] A fifth aspect of the present invention provides a method for selective hydrogenolysis, wherein the method comprises: selectively hydrogenolyzing the reactants in the presence of the catalyst described in the first or third aspect.

[0026] The beneficial effects achieved through the above technical solution are as follows:

[0027] (1) The Pt-W-based catalyst provided by the present invention has high catalytic activity and high stability, and can operate stably for a long period of time.

[0028] (2) In this invention, preferably, the preparation method of the Pt-W-based catalyst is simple. By coating Pt nanoparticles with alumina, the loss of Pt nanoparticles is reduced. The preparation method is simple and the raw materials are widely available. The catalyst obtained is used for selective hydrogenolysis to diols and has high reactant conversion rate and high target product selectivity. Attached Figure Description

[0029] Figure 1 This is a STEM image of the Pt@Al2O3 material without W oxide loading in Example 1. Detailed Implementation

[0030] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0031] The first aspect of the present invention provides a Pt-W-based catalyst, wherein the catalyst comprises Pt nanoparticles, alumina, and W oxide;

[0032] The Pt nanoparticles are confined in alumina, and the W oxide is loaded on the surface of alumina.

[0033] In this invention, the Pt-W-based catalyst exhibits high catalytic activity and good stability. By confining Pt nanoparticles within an alumina structure, the alumina coating of Pt nanoparticles reduces the loss of Pt nanoparticles during catalyst use, significantly improving catalyst stability. Furthermore, the W oxide loaded onto the alumina surface enhances catalyst activity.

[0034] In this invention, the confinement of Pt nanoparticles within alumina refers to the Pt nanoparticles being coated within the alumina framework structure. In this invention, the alumina framework without loaded W oxides is observed using transmission electron microscopy, for example... Figure 1 As shown, Pt particles are uniformly distributed in the alumina framework. Further characterization using ICP and XPS to test the Pt content in the catalyst bulk phase and catalyst surface shows that the Pt content in the catalyst bulk phase is higher than that on the catalyst surface, indicating that Pt nanoparticles are not only loaded on the catalyst surface, but also a considerable portion is uniformly coated in the alumina framework.

[0035] According to the present invention, preferably, the average particle size of the Pt nanoparticles is 0.5-6 nm, for example, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 6 nm, or any range between the two, preferably 2-4 nm. In this invention, the average particle size of the Pt nanoparticles is measured by transmission electron microscopy (TEM), and the average value is taken from the particle size of 100 randomly measured Pt nanoparticles in the TEM image. In this invention, the relatively small average particle size of the Pt nanoparticles allows for uniform dispersion within the alumina framework, which helps to improve catalytic activity.

[0036] According to the present invention, preferably, the Pt nanoparticles have a mass percentage content of 0.3-4 wt% based on the total weight of the catalyst, for example, 0.3 wt%, 0.5 wt%, 0.8 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, or any range between the two, preferably 0.5-3 wt%.

[0037] According to the present invention, preferably, the content of W oxide is 0.3-10% by weight, more preferably 3-8% by weight, based on the total weight of the catalyst.

[0038] In this invention, the mass percentages of W oxide, Pt nanoparticles, and alumina in the catalyst were determined by ICP method.

[0039] In this invention, preferably, the alumina has a mass percentage content of 86-99.4 wt%, more preferably 90-96.5 wt%.

[0040] In this invention, W oxide is uniformly dispersed on the surface of alumina, and loading a small amount of W oxide can effectively improve the catalytic activity of the catalyst.

[0041] A second aspect of the present invention provides a method for preparing a Pt-W-based catalyst, wherein the method comprises:

[0042] (1) Load Pt nanoparticles onto an organic framework to obtain a pre-formed Pt-containing organic framework;

[0043] (2) Grow an organic framework on the surface of the pre-formed Pt-containing organic framework in step (1) to obtain an organic framework for encapsulating Pt particles.

[0044] (3) Fill the organic framework of the encapsulated Pt particles obtained in step (2) with alumina to obtain Pt@Al2O3 material;

[0045] (4) Load W oxide onto the surface of Pt@Al2O3 material and perform heat treatment to obtain Pt-W-based catalyst.

[0046] In this invention, preferably, the preparation method of the Pt-W-based catalyst is simple and the raw materials are easy to obtain. Pt nanoparticles are loaded onto an organic framework, an organic framework is grown on the surface of the organic framework to encapsulate the Pt nanoparticles, and after filling the organic framework with alumina, W oxide is loaded to obtain the Pt-W-based catalyst, which can reduce the loss of Pt nanoparticles in the catalyst during use.

[0047] According to the present invention, preferably, the preparation method of the Pt nanoparticles is not particularly limited, as long as Pt nanoparticles with an average particle size meeting the aforementioned requirements are obtained. According to a preferred embodiment of the present invention, in step (1), the preparation method of the Pt nanoparticles includes:

[0048] After a first heating of a mixture containing a platinum source and an organic solvent, it is mixed with a reducing agent and then heated a second time to obtain Pt nanoparticles.

[0049] According to the present invention, the type and source of the platinum source are not particularly limited, and are platinum-containing compounds conventional in the art. Preferably, the platinum source is selected from at least one of platinum acetylacetonate, chloroplatinic acid, platinum nitrate imine, and potassium chloroplatinate.

[0050] According to the present invention, preferably, the amount of organic solvent used is 100-300 mL, more preferably 120-200 mL, based on 1 g of the platinum source.

[0051] According to the present invention, the type and source of the organic solvent are not particularly limited, and are conventional organic solvents in the art. Preferably, the organic solvent is selected from at least one of oleylamine, cyclohexylamine, and benzidine.

[0052] According to the present invention, the amount of reducing agent is not particularly limited. Preferably, the amount of reducing agent is 0.5-2g, more preferably 1-1.5g, based on 1g of the mass of the platinum source.

[0053] According to the present invention, the type and source of the reducing agent are not particularly limited, and it is a compound conventionally used as a reducing agent in the art. Preferably, the reducing agent is selected from at least one of borane-tert-butylamine complex, borane-pyridine complex, and borane-morpholine complex. In the present invention, the above-mentioned reducing agent is used to reduce a platinum source to obtain Pt nanoparticles with a more uniform average particle size distribution.

[0054] According to the present invention, preferably, the conditions for the first heating include: a heating temperature of 90-150°C, more preferably 100-120°C; and a heating time of 10-120 min, more preferably 20-90 min. In the present invention, trace amounts of water are removed by the first heating.

[0055] In this invention, preferably, the preparation method of the Pt nanoparticles further includes: after a first heating, cooling to 90-110°C, adding a reducing agent, and then performing a second heating.

[0056] According to the present invention, preferably, the conditions for the second heating include: a heating temperature of 100-180°C, more preferably 120-150°C; and a heating time of 1-6 hours, more preferably 2-4 hours.

[0057] In this invention, preferably, the method for preparing the Pt nanoparticles further includes: after the second heating is completed, cooling to room temperature to precipitate Pt nanoparticles; after centrifugation and washing, suspending the Pt nanoparticles in an organic solvent to obtain a suspension containing Pt nanoparticles. Preferably, anhydrous ethanol is used for precipitation, and the organic solvent is selected from at least one of propane, hexane, and n-hexane.

[0058] In this invention, preferably, the amount of Pt nanoparticles and organic solvent used in the suspension containing Pt nanoparticles is not particularly limited, and those skilled in the art can adjust the amount of organic solvent used in the suspension according to the content of Pt nanoparticles.

[0059] In this invention, the terms "first," "second," "third," and "fourth" are not used to limit the order of events, but only to distinguish different products and steps.

[0060] According to the present invention, preferably, the type and source of the organic framework are not particularly limited, and it can be commercially available or prepared by existing methods, referring to conventional crystalline porous polymer materials (POF) in the art, which are composed of organic molecules linked by covalent bonds. According to a preferred embodiment of the present invention, in step (1), the method for preparing the organic framework includes: degassing a mixture containing an amine compound, a precursor and an organic solvent, followed by a third heating, to obtain a solid product as the organic framework.

[0061] According to the present invention, the type and source of the amine compound are not particularly limited, and are conventional amine-containing compounds in the art. Preferably, the amine compound is selected from at least one of melamine, melamine monoamide, and cyanuric acid diamide.

[0062] According to the present invention, the type and source of the precursor are not particularly limited, and are compounds conventional in the art that react with amine compounds to form an organic skeleton. Preferably, the precursor is selected from at least one of terephthalaldehyde, 2,3-dihydroxyterephthalaldehyde, and 2,5-dihydroxyterephthalaldehyde.

[0063] According to a preferred embodiment of the present invention, the amine compound that generates the organic framework is melamine, and the precursor is terephthalaldehyde.

[0064] In this invention, an organic framework is synthesized using amine compounds and precursors as substrates. The organic framework has a porous structure, which is beneficial for loading Pt nanoparticles into the framework structure and providing support for the Pt nanoparticles.

[0065] According to the present invention, preferably, the mass ratio of the amine compound to the precursor in the mixture is 0.1-5:1, more preferably 0.5-2:1.

[0066] In this invention, preferably, the type and source of the organic solvent are not particularly limited, and it is a conventional organic solvent in the art. Preferably, the organic solvent is selected from at least one of dimethyl sulfoxide, chloroform, and acetone.

[0067] In this invention, preferably, based on the sum of the amounts of the amine compound and the precursor used being 1g, the amount of organic solvent used in the mixture is 10-60mL, more preferably 15-50mL.

[0068] In this invention, preferably, the degassing conditions include: degassing at room temperature for 10-30 minutes, more preferably 15-25 minutes. Preferably, the method further includes rinsing the mixture after degassing with a protective atmosphere, wherein the protective atmosphere is nitrogen and / or helium.

[0069] According to the present invention, preferably, the third heating conditions include: a heating rate of 10-30℃ / min, preferably 15-25℃ / min; a heating temperature of 120-240℃, preferably 160-220℃; and a heating time of 30-96h, preferably 48-84h.

[0070] In this invention, preferably, the method for preparing the organic framework further includes: washing and drying the product after a third heating process to obtain the organic framework. The washing and drying methods are not particularly limited, but washing with ethanol and / or acetone is preferred. The drying conditions include: drying under vacuum at a temperature of 60-90°C for 12-36 hours.

[0071] According to the present invention, the loading method is not particularly limited, and those skilled in the art can use conventional loading methods in the art to load Pt nanoparticles onto an organic framework. According to a preferred embodiment of the present invention, the loading method includes: in step (1), the loading method includes: mixing Pt nanoparticles with an organic framework, performing solid-liquid separation, and subjecting the obtained solid product to a first calcination to obtain a pre-formed Pt-containing organic framework.

[0072] According to a preferred embodiment of the present invention, Pt nanoparticles suspended in an organic solvent are mixed with a dispersant containing an organic framework. The mixing method is not particularly limited, but it is preferred that the Pt nanoparticles suspended in the organic solvent be added to the dispersant containing the organic framework.

[0073] In this invention, preferably, the dispersant containing an organic framework comprises an organic framework and a dispersant. Preferably, the dispersant comprises 2-methyltetrahydrofuran and hexane, wherein the volume ratio of 2-methyltetrahydrofuran to hexane is 1:5-10.

[0074] In this invention, preferably, based on a volume of 100 mL of the dispersant, the amount of the organic framework used is 1-10 g, more preferably 2-6 g.

[0075] According to the present invention, preferably, the mass ratio of the Pt nanoparticles to the organic framework is 0.005-0.5:1, for example, 0.005:1, 0.008:1, 0.01:1, 0.015:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.08:1, 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, or any range between the two, preferably 0.01-0.2:1.

[0076] In this invention, preferably, step (1) further includes: mixing Pt nanoparticles with an organic framework, followed by stirring, solid-liquid separation, and drying.

[0077] In this invention, preferably, the conditions for stirring, solid-liquid separation, and drying are not particularly limited, and those skilled in the art can adjust them adaptively according to the loading conditions. When the supernatant is observed to be colorless, it indicates that the Pt particles are completely loaded onto the organic framework. Preferably, the stirring conditions include: stirring time of 10-30 min and stirring speed of 500-800 rpm.

[0078] In this invention, centrifugation is preferably used to separate solids and liquids and remove the solvent.

[0079] In this invention, preferably, the drying conditions include: a drying temperature of 50-100℃, more preferably 60-80℃, and a drying time of 1-6h, more preferably 2-4h.

[0080] According to the present invention, preferably, the conditions for the first calcination include: calcination at a temperature of 200-500°C, preferably 250-400°C, under an oxygen-containing atmosphere, and a calcination time of 10-60 min, preferably 15-40 min. In the present invention, calcination under the above conditions removes the organic ligands to obtain a pre-formed Pt-containing organic framework, wherein the oxygen-containing atmosphere is oxygen and / or air.

[0081] According to the present invention, preferably, step (2) includes: mixing a pre-formed Pt-containing organic framework with a mixture containing an amine compound, a precursor and an organic solvent, and performing a fourth heating to obtain an organic framework for encapsulating Pt particles.

[0082] In this invention, the types of amine compounds, precursors and organic solvents in the mixture containing amine compounds, precursors and organic solvents are not particularly limited, but are preferably the same as those mentioned above, and will not be repeated here.

[0083] According to the present invention, preferably, the mass ratio of the preformed Pt-containing organic framework to the amine compound and the precursor is 1:1-10, more preferably 1:3-7.

[0084] In this invention, preferably, in step (2), the mass ratio of the amine compound to the precursor is 0.1-5:1, more preferably 0.5-2:1. The amine compound and precursor are added according to the above ratio to grow an additional organic framework on the surface of the pre-formed Pt-containing organic framework, encapsulating the Pt nanoparticles in the framework, thus obtaining an organic framework encapsulating Pt particles.

[0085] According to the present invention, preferably, in step (2), the amount of organic solvent used is 10-60 mL, more preferably 15-50 mL, based on the sum of the amounts of amine compounds and precursors used being 1 g.

[0086] In this invention, preferably, the conditions for the fourth heating include: a heating temperature of 120-240℃, more preferably 150-210℃, and a heating time of 12-36h, more preferably 16-24h.

[0087] According to the present invention, preferably, in step (3), the filling process includes: mixing the organic framework of encapsulating Pt particles with an organic solution containing an aluminum source, and then performing vacuum drying and a second calcination to obtain Pt@Al2O3 material.

[0088] In this invention, through the above-described filling process, alumina is used to replace the organic framework to coat Pt nanoparticles, reducing the loss of Pt nanoparticles in the catalyst during use and resulting in a more stable structure that helps improve the stability of the catalyst.

[0089] According to a preferred embodiment of the present invention, the mixing process includes: adding the organic framework encapsulating Pt particles to an organic solution containing an aluminum source, followed by ultrasonic treatment and evaporation. Preferably, the ultrasonic treatment time is 5-20 minutes.

[0090] In this invention, the evaporation conditions and equipment are not particularly limited. Preferably, the evaporation conditions include: an evaporation temperature of 40-70°C and an evaporation time of 0.5-3 hours. Preferably, the evaporation is carried out in a rotary evaporator.

[0091] According to the present invention, preferably, the amount of aluminum source is calculated based on alumina, and the mass ratio of the organic framework of the encapsulated Pt particles to the aluminum source is 1:1-20, preferably 1:2-10.

[0092] In this invention, the aluminum source is a conventional aluminum source in the art, and preferably, the aluminum source is aluminum nitrate and / or aluminum sulfate.

[0093] In this invention, preferably, the solvent in the aluminum-containing organic solution is selected from at least one of ethanol, propanol, and isopropanol. Preferably, based on a solvent volume of 100 mL in the aluminum-containing organic solution, and the aluminum source being calculated as alumina, the amount of aluminum source used is 1-10 g, more preferably 2-6 g.

[0094] In this invention, the vacuum drying conditions can be selected within a wide range, and those skilled in the art can adapt and adjust the drying temperature and drying time. Preferably, the vacuum drying conditions include: under vacuum conditions, the drying temperature is 60-100℃ and the drying time is 12-36h.

[0095] According to the present invention, preferably, the second calcination conditions include: a calcination temperature of 400-800℃, preferably 500-700℃; a calcination time of 2-8h, preferably 3-6h; and a heating rate of 0.1-2℃ / min, preferably 0.5-1℃ / min.

[0096] According to the present invention, preferably, step (4) includes: mixing the Pt@Al2O3 material with a solution containing a tungsten source and performing heat treatment.

[0097] According to the present invention, the type and source of the tungsten source are not particularly limited, and are conventional tungsten sources in the art. Preferably, the tungsten source is selected from at least one of ammonium metatungstate, ammonium paratungstate, and sodium tungstate.

[0098] According to the present invention, preferably, the tungsten source, calculated as W oxide, has a mass ratio of tungsten source to Pt@Al2O3 material of 0.003-0.1:1, for example 0.003:1, 0.005:1, 0.008:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, or any range between the two, preferably 0.03-0.08:1.

[0099] In this invention, preferably, step (4) further includes: drying the mixture obtained by mixing Pt@Al2O3 material with a tungsten-containing source solution, and then heat-treating the resulting solid product. The drying conditions are not particularly limited, and those skilled in the art can adjust them accordingly.

[0100] According to the present invention, preferably, the heat treatment conditions include: a heat treatment temperature of 200-800℃, for example, 200℃, 300℃, 400℃, 500℃, 600℃, 700℃, 800℃, or any range between the two, preferably 300-600℃; and a heat treatment time of 1-10h, for example, 1h, 2h, 3h, 4h, 5h, 6h, 8h, 10h, or any range between the two, preferably 2-6h. In the present invention, loading W oxides onto the surface of Pt@Al2O3 material through heat treatment helps to improve the catalytic activity of the catalyst.

[0101] The third aspect of this invention provides a Pt-W-based catalyst prepared by the preparation method described in the second aspect.

[0102] The fourth aspect of this invention provides the application of the Pt-W-based catalyst described in the first or third aspect in a hydrogenolysis reaction.

[0103] In this invention, preferably, the Pt-W-based catalyst is used in a hydrogenolysis reaction. By encapsulating Pt nanoparticles with Al2O3 material, the loss of Pt nanoparticles during the reaction is reduced, thereby improving the catalyst stability. Furthermore, W oxide is loaded onto the catalyst surface to enhance the hydrogenolysis reaction activity of the catalyst.

[0104] A fifth aspect of the present invention provides a method for selective hydrogenolysis, wherein the method comprises: selectively hydrogenolyzing the reactants in the presence of the catalyst described in the first or third aspect.

[0105] According to the present invention, preferably, the reaction raw materials are selected from at least one of glycerol, tetrahydrofurfuryl alcohol and tetrahydrofurandiethanol.

[0106] In this invention, the above-mentioned catalyst is used to selectively hydrogenate the reactants glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandimethyl alcohol to synthesize 1,3-propanediol, 1,5-pentanediol, and 1,6-hexanediol. The reaction conditions are easy to control, the catalyst has high activity, and the reactant conversion rate and target product selectivity are high. After long-term operation, the loss rate of precious metal Pt in the catalyst is low, and the reactant conversion rate and target product selectivity remain at a high level.

[0107] According to the present invention, the conditions for the selective hydrogenolysis reaction can be selected within a wide range. Preferably, the reaction conditions for the selective hydrogenolysis reaction include: a reaction temperature of 120-180°C, more preferably 140-170°C; and a hydrogen pressure of 1-8 MPa, more preferably 3-6 MPa.

[0108] According to the present invention, the apparatus for the reaction is not particularly limited; preferably, the reaction is carried out in a fixed-bed reactor with a liquid hourly space velocity of 0.05-5 h⁻¹. -1Preferably 0.1-3h -1 .

[0109] According to a preferred embodiment of the present invention, the aqueous solution of the reactants is contacted with a catalyst to carry out a selective hydrogenolysis reaction.

[0110] In this invention, preferably, the concentration of the aqueous solution of the reaction raw materials is 10-95% by weight, more preferably 20-60% by weight.

[0111] In this invention, the liquid phase refers to the aqueous solution of the reaction raw materials.

[0112] The present invention will be described in detail below through examples and comparative examples. Unless otherwise specified, all reagents used in the following examples and comparative examples are commercially available.

[0113] The room temperature is 25℃.

[0114] Example 1

[0115] (1-1) 200 mg of platinum acetylacetonate was dissolved in 30 mL of oleylamine (OAm), and heated at 110 °C for 30 minutes to remove trace amounts of water, then cooled to 100 °C. 2 mL of oleylamine solution containing 200 mg of borane-tert-butylamine complex (reducing agent) was added to the above solution, and the temperature was then increased to 140 °C and stirred for 4 hours. After cooling to room temperature, 60 mL of anhydrous ethanol was added to precipitate platinum nanoparticles from the mixture. After centrifugation and washing, the Pt nanoparticles were suspended in hexane.

[0116] (1-2) In a three-necked flask, 9.3 g of melamine and 15 g of terephthalaldehyde were added to 495 mL of dimethyl sulfoxide. The mixture was degassed at room temperature for 15 minutes, rinsed with nitrogen, heated to 180 °C at a rate of 20 °C / min, and held at this temperature for 72 hours. The resulting solid product was washed three times with acetone and dried under vacuum at 80 °C for 24 hours to obtain the organic framework (POF).

[0117] (1-3) Under stirring at 600 rpm, 4.8 g of the organic framework was dispersed in 120 mL of a mixed solution containing 2-methyltetrahydrofuran and hexane (volume ratio 1:9). A hexane suspension containing 96 mg of Pt nanoparticles was added dropwise to the mixed solution, and the mixture was stirred for 20 minutes to load the Pt nanoparticles onto the organic framework. The observation of a colorless supernatant indicated that the Pt nanoparticles were completely adsorbed. The solvent was then removed by centrifugation (8586 g, 3 min), and the mixture was dried at 80 °C for 3 h. The organic ligands were removed by calcination in air at 300 °C for 20 min, yielding a pre-formed Pt-containing organic framework (approximately 4.5 g).

[0118] (2) Mix 4.5g of pre-formed Pt-containing organic framework with 366mL of dimethyl sulfoxide solution containing 7.1g of melamine and 11.2g of terephthalaldehyde to obtain a mixture. Heat to 180°C and heat for 24 hours to obtain a solid product. Wash the solid product three times with acetone to obtain the organic framework encapsulating Pt particles.

[0119] (3) Dissolve 90g of Al(NO3)3·9H2O in 500mL of ethanol, add 6g of the organic framework encapsulating Pt particles, sonicate for 10 minutes, slowly remove ethanol in a rotary evaporator at 60℃ for 1 hour, and vacuum dry at 80℃ for 24 hours. Calcine the sample again at 600℃ with a heating rate of 0.5℃ / min for 5 hours to obtain Pt@Al2O3 material.

[0120] (4) Weigh ammonium metatungstate and dissolve it in 10 mL of water. Add 10 g of Pt@Al2O3 material to the above solution. The mass ratio of tungsten trioxide to Pt@Al2O3 material is 0.05:1 based on the mass of W oxide. After drying for 8 hours, heat-treat at 450℃ for 3 hours to obtain Pt-W based catalyst A1.

[0121] Figure 1 This is a STEM image of the Pt@Al2O3 material synthesized in step (3) of Example 1. The white bright spots in the image are Pt nanoparticles. Figure 1 As can be seen, Pt particles are uniformly distributed in the Pt@Al2O3 material. Further characterization of the prepared catalyst Al by XPS and ICP elemental analysis is shown in Table 1. Table 1 shows that the Pt content in the catalyst bulk phase is 0.99 wt%, while the Pt content on the catalyst surface is only 0.05 wt%, indicating that Pt nanoparticles not only exist on the catalyst surface but are also largely confined within the alumina, with Pt nanoparticles uniformly coated within the aluminum framework.

[0122] Table 1. ICP and XPS elemental analysis results of Pt@Al2O3 materials

[0123]

[0124] Example 2

[0125] The catalyst was prepared according to the method of Example 1, except that in steps (1-3), the amount of Pt nanoparticles was changed and the mass ratio of Pt nanoparticles to organic framework was 0.015:1. Other conditions were the same as in Example 1, and Pt-W based catalyst A2 was obtained.

[0126] Example 3

[0127] (1-1) 208 mg of chloroplatinic acid was dissolved in 30 mL of oleylamine (OAm), and heated at 120 °C for 30 minutes to remove trace amounts of water, then the temperature was cooled to 100 °C. 2 mL of an oleylamine solution containing 180 mg of a borane-pyridine complex (reducing agent) was added to the above solution, and the temperature was then increased to 150 °C and stirred for 3 hours. After cooling to room temperature, 60 mL of anhydrous ethanol was added to precipitate Pt nanoparticles from the mixture. After centrifugation and washing, the Pt nanoparticles were suspended in hexane.

[0128] (1-2) In a three-necked flask, 10 g of melamine and 13 g of 2,3-dihydroxyterephthalaldehyde were added to 500 mL of chloroform (organic solvent). The mixture was degassed at room temperature for 15 min, rinsed with nitrogen, heated to 190 °C at a rate of 15 °C / min, and held at this temperature for 48 h. The resulting solid product was washed three times with acetone and dried under vacuum at 80 °C for 24 h to obtain the organic framework (POF).

[0129] (1-3) Under stirring at 500 rpm, 5 g of the organic framework was dispersed in 120 mL of a mixed solution containing 2-methyltetrahydrofuran and hexane (volume ratio 1:8). A hexane suspension containing 96 mg of Pt nanoparticles was added dropwise to the mixed solution, and the mixture was stirred for 20 minutes to load the Pt nanoparticles onto the organic framework. The observation of a colorless supernatant indicated that the Pt nanoparticles were completely adsorbed. The solvent was then removed by centrifugation (8586 g, 3 min), and the mixture was dried at 80 °C for 3 h. The organic ligands were removed by first calcination in air at 280 °C for 30 min, yielding a pre-formed Pt-containing organic framework.

[0130] (2) Mix 4.6g of pre-formed Pt-containing organic framework with 450mL of chloroform containing 7.2g of melamine and 11.8g of 2,3-dihydroxyterephthalaldehyde to obtain a mixture. Heat the mixture to 180°C for 24 hours to obtain a solid product. Wash the solid product three times with acetone to obtain the organic framework encapsulating Pt particles.

[0131] (3) Dissolve 60g of Al(NO3)3·9H2O in 500mL of ethanol, add 4g of the organic framework encapsulating Pt particles, sonicate for 10 minutes, slowly remove ethanol in a rotary evaporator at 60℃ for 1 hour, and vacuum dry at 80℃ for 24 hours. Calcine the sample again at 550℃ with a heating rate of 0.8℃ / min for 5 hours to obtain Pt@Al2O3 material.

[0132] (4) Weigh ammonium metatungstate and dissolve it in 12 mL of water. Add 10 g of Pt@Al2O3 material to the above solution. The mass ratio of tungsten trioxide to Pt@Al2O3 material is 0.06:1 based on the mass of W oxide. After drying for 8 hours, heat-treat at 500℃ for 2 hours to obtain Pt-W based catalyst A3.

[0133] Example 4

[0134] The catalyst was prepared according to the method of Example 1, except that the amount of ammonium metatungstate added in step (4) was changed so that the mass ratio of tungsten trioxide to Pt@Al2O3 material was 0.09:1 based on the mass of W oxide. Other conditions were the same as in Example 1, and Pt-W based catalyst A4 was obtained.

[0135] Example 5

[0136] The catalyst was prepared according to the method of Example 1, except that the encapsulation in step (2) was not performed, and 4.5g of the pre-formed Pt-containing organic framework was directly used in step (3) to obtain the Pt-W-based catalyst A5.

[0137] Comparative Example 1

[0138] The Pt component is loaded onto the surface of alumina using a conventional equal-volume impregnation method, rather than being encapsulated within the alumina.

[0139] Specific steps: 12g of Sasol PURAL BT alumina support (alumina source: manufacturer: Sasol, model: PURAL SB) was calcined at 600℃ for 3 hours. 1g of ammonium metatungstate was dissolved in 7.5mL of water to obtain a solution. The calcined alumina support was added to the above solution in an equal volume for impregnation. After stirring for 10 minutes, it was dried at 80℃ for 8 hours and then calcined at 550℃ for 3 hours to obtain a white powder containing W oxide. 200mg of platinum acetylacetonate was dissolved in 7mL of water. 10g of the white powder containing W oxide was added to the above solution in an equal volume for impregnation. After drying at 80℃ for 6 hours, it was calcined at 450℃ for 3 hours to obtain catalyst D1.

[0140] Comparative Example 2

[0141] The method is the same as in Example 1, except that step (4) is omitted, and the Pt@Al2O3 material obtained in step (3) is used as catalyst D2.

[0142] Comparative Example 3

[0143] The method of Example 1 is the same, except that steps (1-2), (1-3) and step (2) are omitted, and Pt nanoparticles are directly coated with alumina without the participation of an organic framework.

[0144] Specifically: (1) Pt nanoparticles were suspended in hexane according to the method of Example (1-1) to obtain a Pt nanoparticle suspension;

[0145] (2) The Pt nanoparticle suspension was mixed with 500 mL of ethanol solution containing 90 g of Al(NO3)3·9H2O, and ultrasonicated for 10 minutes. The ethanol was then slowly removed in a rotary evaporator at 60 °C for 1 hour, and vacuum dried at 80 °C for 24 hours. The sample was then calcined for 5 hours at 600 °C with a heating rate of 0.5 °C / min to obtain the intermediate product.

[0146] (3) Weigh ammonium metatungstate and dissolve it in 10 mL of water. Add 10 g of intermediate product to the above solution. The mass ratio of tungsten trioxide to intermediate product is 0.05:1 based on the mass of W oxide. After drying for 8 hours, heat-treat at 450 °C for 3 hours to obtain Pt-W based catalyst D3.

[0147] The contents of each component in the catalyst and the catalyst physical properties are shown in Table 2. The contents of each component were obtained by ICP test.

[0148] Table 2

[0149]

[0150] Note: The ICP test results for Pt nanoparticles, W oxides, and alumina in the catalyst may have errors, and their sum may not equal 100wt%.

[0151] As can be seen from the results in Table 2, the catalyst prepared according to the preparation method provided by the present invention has a uniform particle size distribution of Pt nanoparticles. In contrast, Comparative Example 3 did not coat the Pt nanoparticles with an organic framework, and the Pt particles in the resulting catalyst agglomerated, resulting in a poor coating effect.

[0152] Test case

[0153] (1) Weigh 1g of the catalyst obtained above and place it in a fixed-bed reactor. Under the conditions of reaction temperature of 160℃ and hydrogen pressure of 5MPa, the reaction is carried out at a rate of 1.5h. -1 A 20 wt% aqueous glycerol solution was introduced at a space velocity of 100 h. Liquid samples were collected from the outlet at the initial stage (first 4 hours) and at 240 h. The target product was 1,3-propanediol, and gas chromatography analysis was performed. Catalyst parameters and reaction results are listed in Table 3.

[0154] Table 3

[0155]

[0156]

[0157] (2) Weigh 1g of the catalyst obtained above and place it in a fixed-bed reactor. Under the conditions of reaction temperature of 160℃ and hydrogen pressure of 5MPa, the catalyst is reacted at a rate of 0.1h. -1 A 20 wt% tetrahydrofurfuryl alcohol aqueous solution was introduced at a space velocity of 100 h. Liquid samples were collected from the outlet at the initial stage (first 4 hours) and at 240 h. The target product was 1,5-pentanediol, and gas chromatography analysis was performed. Catalyst parameters and reaction results are listed in Table 4.

[0158] Table 4

[0159]

[0160]

[0161] (3) Weigh 1g of the catalyst obtained above and place it in a fixed-bed reactor. Under the conditions of reaction temperature of 160℃ and hydrogen pressure of 5MPa, the catalyst is reacted at a rate of 0.1h. -1 A 20 wt% tetrahydrofurandiethanol aqueous solution was introduced at a space velocity of 0.5 h. Liquid samples were collected from the outlet at the initial stage (first 4 hours) and at 240 h. The target product was 1,6-hexanediol, and gas chromatography analysis was performed. Catalyst parameters and reaction results are listed in Table 5.

[0162] Table 5

[0163]

[0164] As can be seen from the results in Tables 3, 4, and 5, the catalyst prepared using the embodiments of the present invention, for the selective hydrogenolysis of secondary hydroxyl groups of glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandiethanol to synthesize 1,3-propanediol, 1,5-pentanediol, and 1,6-hexanediol, exhibits higher stability compared to catalysts synthesized by existing methods. It can significantly suppress the loss of the precious metal Pt, laying the foundation for promoting the industrial application of bio-based high-end glycol polyester monomers.

[0165] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A Pt-W-based catalyst, characterized in that, The catalyst comprises Pt nanoparticles, alumina, and W oxide; The Pt nanoparticles are confined in alumina, and the W oxide is loaded on the surface of alumina.

2. The catalyst according to claim 1, wherein, The average particle size of the Pt nanoparticles is 0.5-6 nm, preferably 2-4 nm; Preferably, the Pt nanoparticles comprise 0.3-4% by weight, more preferably 0.5-3% by weight, based on the total weight of the catalyst.

3. The catalyst according to claim 1 or 2, wherein, The content of W oxide is 0.3-10% by weight, preferably 3-8% by weight, based on the total weight of the catalyst.

4. A method for preparing a Pt-W-based catalyst, characterized in that, The method includes: (1) Load Pt nanoparticles onto an organic framework to obtain a pre-formed Pt-containing organic framework; (2) Grow an organic framework on the surface of the pre-formed Pt-containing organic framework in step (1) to obtain an organic framework for encapsulating Pt particles. (3) Fill the organic framework of the encapsulated Pt particles obtained in step (2) with alumina to obtain Pt@Al2O3 material; (4) Load W oxide onto the surface of Pt@Al2O3 material and perform heat treatment to obtain Pt-W-based catalyst.

5. The preparation method according to claim 4, wherein, In step (1), the method for preparing the Pt nanoparticles includes: After a first heating of a mixture containing a platinum source and an organic solvent, it is mixed with a reducing agent and heated a second time to obtain Pt nanoparticles. Preferably, the platinum source is selected from at least one of platinum acetylacetonate, chloroplatinic acid, platinum nitrate imine, and potassium chloroplatinate; Preferably, based on 1g of the platinum source, the amount of organic solvent used is 100-300mL, more preferably 120-200mL; Preferably, the organic solvent is selected from at least one of oleylamine, cyclohexylamine, and benzidine; Preferably, based on 1g of the platinum source, the amount of the reducing agent is 0.5-2g, more preferably 1-1.5g; Preferably, the reducing agent is selected from at least one of borane-tert-butylamine complex, borane-pyridine complex, and borane-morpholine complex; Preferably, the conditions for the first heating include: a heating temperature of 90-150℃, more preferably 100-120℃; and a heating time of 10-120 min, more preferably 20-90 min. Preferably, the conditions for the second heating include: a heating temperature of 100-180℃, more preferably 120-150℃; and a heating time of 1-6 hours, more preferably 2-4 hours.

6. The preparation method according to claim 4 or 5, wherein, The organic framework is a crystalline porous polymer material composed of organic molecules linked by covalent bonds; Preferably, in step (1), the method for preparing the organic framework includes: degassing a mixture containing amine compounds, precursors and organic solvents and then subjecting it to a third heating to obtain a solid product as the organic framework; Preferably, the amine compound is selected from at least one of melamine, melamine monoamide, and cyanuric acid diamide; Preferably, the precursor is selected from at least one of terephthalaldehyde, 2,3-dihydroxyterephthalaldehyde, and 2,5-dihydroxyterephthalaldehyde; Preferably, the mass ratio of the amine compound to the precursor in the mixture is 0.1-5:1, more preferably 0.5-2:1; Preferably, the third heating conditions include: a heating rate of 10-30℃ / min, preferably 15-25℃ / min; a heating temperature of 120-240℃, preferably 160-220℃; and a heating time of 30-96h, preferably 48-84h.

7. The preparation method according to any one of claims 4-6, wherein, In step (1), the loading method includes: mixing Pt nanoparticles with an organic framework, separating solid and liquid, and then calcining the resulting solid product to obtain a pre-formed Pt-containing organic framework. Preferably, the mass ratio of Pt nanoparticles to the organic framework is 0.005-0.5:1, more preferably 0.01-0.2:1; Preferably, the conditions for the first calcination include: calcination temperature of 200-500℃, preferably 250-400℃, under an oxygen-containing atmosphere, and calcination time of 10-60min, preferably 15-40min.

8. The preparation method according to any one of claims 4-7, wherein, Step (2) includes: mixing the pre-formed Pt-containing organic framework with a mixture containing amine compounds, precursors and organic solvents, and performing a fourth heating to obtain an organic framework for encapsulating Pt particles. Preferably, the mass ratio of the preformed Pt-containing organic framework to the amine compound and the precursor is 1:1-10, more preferably 1:3-7; Preferably, in step (2), the amount of organic solvent used is 10-60 mL, preferably 15-50 mL, based on the sum of the amounts of amine compounds and precursors used being 1 g.

9. The preparation method according to any one of claims 4-8, wherein, In step (3), the filling process includes: mixing the organic framework of the encapsulated Pt particles with an organic solution containing an aluminum source, and then performing vacuum drying and a second calcination to obtain Pt@Al2O3 material; Preferably, the amount of aluminum source is calculated based on alumina, and the mass ratio of the organic framework of the encapsulated Pt particles to the aluminum source is 1:1-20, preferably 1:2-10; Preferably, the aluminum source is aluminum nitrate and / or aluminum sulfate; Preferably, the second calcination conditions include: a calcination temperature of 400-800℃, preferably 500-700℃; a calcination time of 2-8h, preferably 3-6h; and a heating rate of 0.1-2℃ / min, preferably 0.5-1℃ / min.

10. The preparation method according to any one of claims 4-9, wherein, Step (4) includes: mixing the Pt@Al2O3 material with a solution containing a tungsten source and performing heat treatment; Preferably, the tungsten source is selected from at least one of ammonium metatungstate, ammonium paratungstate, and sodium tungstate; Preferably, the tungsten source, calculated as W oxide, has a mass ratio of tungsten source to Pt@Al2O3 material of 0.003-0.1:1, more preferably 0.03-0.08:1; Preferably, the heat treatment conditions include: a heat treatment temperature of 200-800℃, more preferably 300-600℃; and a heat treatment time of 1-10h, more preferably 2-6h.

11. The catalyst prepared by the method according to any one of claims 4-10.

12. The use of the catalyst according to any one of claims 1-3 and 11 in hydrogenolysis reactions.

13. A method for selective hydrogenolysis to produce diols, characterized in that, The method includes: selectively hydrogenating the reactants in the presence of the catalyst described in any one of claims 1-3 and 11; Preferably, the reactants are selected from at least one of glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandiethanol. Preferably, the reaction conditions for the selective hydrogenolysis reaction include: a reaction temperature of 120-180℃, more preferably 140-170℃; and a hydrogen pressure of 1-8 MPa, more preferably 3-6 MPa. Preferably, the reaction is carried out in a fixed-bed reactor with a liquid hourly space velocity (LHSV) of 0.05-5 h⁻¹. -1 Preferably 0.1-3h -1 .